Protecting health personnel in the Covid-19 pandemic - De La Cruz-Vargas, Jhony A. (2020)
The epidemic and pandemic of COVID-19 constitute an unprecedented public health emergency, it arrived in Latin America, first in Brazil, then in Ecuador; The first cases in Peru were registered as of March 6, 2020. The correct response of the Government of Peru decreed a state of national emergency and mandatory social isolation, initially for 14 days, with the aim of reducing the exposure and transmission of the Coronavirus. It assigned economic funds for 3 million poor families in Peru, during social isolation.The repercussions of COVID-19 are huge, at a social, economic, cultural, and educational level, of course, on the country's health system and your staff. Borders, universities, shops, restaurants are closed. The Pension Fund Administrators (AFP for its acronym in Spanish) announced to be affected quickly, generating significant losses to users. All of this is unpredictable and, just the tip of the iceberg.